Personal characteristics of a 21st-century teacher: An analysis of empirical studies of the problem - E. N. Volkova (Russian State Vocational Pedagogical University, 2022)
Introduction. Modern scientific literature lacks evidence-based empirical studies of teacher personality. Singular reviews of the empirical studies related to the teacher personality are fulfilled within the framework of one theoretical model and do not cover results obtained in other directions of research, which does not benefit the practice of modern educational managers, teachers or educational psychologists. This gap might be filled with generalising empirical evidence through analysing international publications on personality of the modern teacher.Aim. The article aims to review empirical studies dedicated to the characteristics of a 21st-century teacher, to understand the existing limitations in the research of teacher personality, and to outline future research directions for the optimisation of today's educational practice.Methods. The review includes the publications selected with searching keywords along with additional descriptors, followed by the analysis of content of relevant publications. The review covers articles published in the last 20 years.Results. The results of empirical studies, which meet the research selection criteria (have representative volumes of research samples and performed using measuring tools with known psychometric properties), allowed the author to distinguish several main clusters for studying teacher personal characteristics. The most prevalent are the studies of teacher personality within the five-factor framework, teacher emotional intelligence and motivation (job motivation, intrinsic motivation and semantic preferences). Within these clusters, the author has identified the tendencies, which demonstrate personal characteristics of a 21st-century teacher and correspond to subjective paradigm of modern education, effective teaching and effective management of education processes.Scientific novelty. The generalisation of results allowed the author to determine the basic personality characteristics of the modern teacher. The presented results reveal the patterns of personality development, work behaviour of a modern teacher and can serve as the basis for further research in the field of educational sciences, personality psychology, labour psychology and educational psychology.Practical significance. The specific historical knowledge about personal characteristics of a 21st-century teacher may serve for strategic and tactical decisions in the field of education management; determine the tactics of managing modern teaching staff; design teacher-centric programmes for the educational psychological services and educational programmes for the training, retraining and advanced training of teachers.